IMPLEMENTASI METODE MIND MAPPING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR SIMBOLIK ANAK DI TAMAN KANAK-KANAK ISLAM NIBRAS PADANG - Radhiyatul Husni; Nur Hazizah; Yulsyofriend; Nurhafizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low ability of symbolic thinking in children is marked by difficulties in connecting symbols with real objects, a lack of skills in expressing ideas symbolically, limited ability to recognize and categorize symbols, weak visual memory, slow understanding of directions and positions, and minimal creativity in creating their own symbols. This research aims to describe the application of the mind mapping method to improve the symbolic thinking abilities of 5–6-year-old children at the Nibras Padang Islamic Kindergarten. The research approach used is qualitative with a descriptive type. Data was collected through observation, interviews, and documentation. The research subjects include class B teachers, the school principal, and students. The research results reveal that the implementation of the mind mapping method is carried out systematically, encompassing the stages of planning, execution, and evaluation. The teacher designs learning activities based on themes that are close to the children's lives, such as the theme 'My Vehicle', and utilizes visual media in the form of pictures, arrows, and symbols that help children connect concrete concepts with symbolic ones. In practice, children actively engage in creating mind maps with the teacher acting as a facilitator. The application of this method results in improved ability for children to recognize, understand, and communicate symbols in a more organized and creative manner. Thus, mind mapping has proven to be effective in developing the symbolic thinking skills of early childhood through enjoyable, visual-based learning that is suitable for their developmental stage.